Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Bourgeoning Impacts of the Coastal Megacities and Potential Ecological Risks of Leachable Heavy Metals in Fine-sediments Fractions along the Egyptian Red Sea Shores - Ahmed Salah-Tantawy; Aldoushy Mahdy; Mahmoud A. Dar; Ching-Fu Lee; Abdelbaset M. A. Abdelreheem (Water, Air, & Soil Pollution, 2024)

A promising non-fullerene acceptor for near-infrared organic photodetectors operating with low dark current and high response speed - Yu-Ching Huang; Zhi-Hao Huang; Tai-Yung Wang; Priyanka Chaudhary; Jen-Fu Hsu; Kun-Mu Lee (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Correction to: Chitosan‑based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu‑Wei Huang; Fang‑Ching Yeh; You‑Ren Ji; Ying‑Fu Su; Ying‑shih Su; Ming‑Hsien Chiang; Shian‑Chiuan Tzeng; Chien‑Yao Fu; Aristine Cheng; Yung‑Chih Wang; Yi‑Tzu Lee (Drug Delivery and Translational Research, 2022)

Biomechanical Evaluation of a Fin-type Implant Compared to Traditional Buttress Plate for the Stabilization of the Posteromedial Fragment in Tibial Plateau Split Fractures - Jian-Chih Chen; Kang-Ping Lin; Tien-Ching Lee; Yin-Chih Fu; Kun-Jhih Lin (Journal of Medical and Biological Engineering, 2021)

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu-Wei Huang; Fang-Ching Yeh; You-Ren Ji; Ying-Fu Su; Ying-shih Su; Ming-Hsien Chiang; Shian-Chiuan Tzeng; Chien-Yao Fu; Aristine Cheng; Yung-Chih Wang; Yi-Tzu Lee (Drug Delivery and Translational Research, 2021)

Taxonomy of the yeast genus Vanderwaltozyma and proposal of Vanderwaltozyma meishanica sp. nov., Vanderwaltozyma huisunica sp. nov., and Vanderwaltozyma molinica sp. nov. - Chin-Feng Chang; Yi-Ru Liu; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Cystobasidium keelungensis sp. nov., a novel mycosporine producing carotenogenic yeast isolated from the sea surface microlayer in Taiwan - Chin-Feng Chang; Ching-Fu Lee; Shiu-Mei Liu (Archives of Microbiology, 2019)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Identifying and characterizing Yarrowia keelungensis sp. nov., an oil-degrading yeast isolated from the sea surface microlayer - Chin-Feng Chang; Chih-Chen Chen; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2013)

Histone deacetylase inhibitor AR-42 enhances E7-specific CD8+ T cell-mediated antitumor immunity induced by therapeutic HPV DNA vaccination - Sung Yong Lee; Zhuomin Huang; Tae Heung Kang; Ruey-Shyang Soong; Jayne Knoff; Ellen Axenfeld; Chenguang Wang; Ronald D. Alvarez; Ching-Shih Chen; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2013)

Trichosporon vanderwaltii sp. nov., an asexual basidiomycetous yeast isolated from soil and beetles - Thabiso E. Motaung; Jacobus Albertyn; Johan L. F. Kock; Ching-Fu Lee; Sung-Oui Suh; Meredith Blackwell; Carolina H. Pohl (Antonie van Leeuwenhoek, 2013)

Molecular genetic diversity of the Saccharomyces yeasts in Taiwan: Saccharomyces arboricola, Saccharomyces cerevisiae and Saccharomyces kudriavzevii - Gennadi I. Naumov; Ching-Fu Lee; Elena S. Naumova (Antonie van Leeuwenhoek, 2013)

Candida sanyaensis sp. nov., an ascomycetous yeast species isolated from soil - Feng-Li Hui; Qiu-Hong Niu; Tao Ke; Ying-Xia Li; Ching-Fu Lee (Antonie van Leeuwenhoek, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Five novel species of the anamorphic genus Candida in the Cyberlindnera clade isolated from natural substrates in Taiwan - Chin-Feng Chang; Yi-Ru Liu; Shan-Fu Chen; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2012)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

Saturnispora serradocipensis sp. nov. and Saturnispora gosingensis sp. nov., two ascomycetous yeasts from ephemeral habitats - Monica R. Canelhas; Anne C. Barbosa; Adriana O. Medeiros; Ching-Fu Lee; Li-Yin Huang; Marc-André Lachance; Carlos A. Rosa (Antonie van Leeuwenhoek, 2011)

Candida asiatica sp. nov., an anamorphic ascomycetous yeast species isolated from natural samples from Thailand, Taiwan, and Japan - Savitree Limtong; Rungluk Kaewwichian; Somjit Am-In; Takashi Nakase; Ching-Fu Lee; Wichien Yongmanitchai (Antonie van Leeuwenhoek, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Candida neustonensis sp. nov., a novel ascomycetous yeast isolated from the sea surface microlayer in Taiwan - Chin-Feng Chang; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2010)

Detrital zircon evidence for the antiquity of Taiwan - Ching-Ying Lan; Tadashi Usuki; Kuo-Lung Wang; Tzen-Fu Yui; Kazuaki Okamoto; Yuan-Hsi Lee; Takafumi Hirata; Yoshitaka Kon; Yuji Orihashi; Juhn G. Liou; Chun-Sun Lee (Geosciences Journal, 2009)

Kazachstania wufongensis sp. nov., an ascosporogenous yeast isolated from soil in Taiwan - Ching-Fu Lee; Cheng-Hsu Yao; Yi-Ru Liu; Shuh-Sen Young; Ku-Shang Chang (Antonie van Leeuwenhoek, 2009)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)